2016
DOI: 10.1371/journal.pone.0148066
|View full text |Cite
|
Sign up to set email alerts
|

High Spatial Resolution Cardiovascular Magnetic Resonance at 7.0 Tesla in Patients with Hypertrophic Cardiomyopathy – First Experiences: Lesson Learned from 7.0 Tesla

Abstract: BackgroundCardiovascular Magnetic Resonance (CMR) provides valuable information in patients with hypertrophic cardiomyopathy (HCM) based on myocardial tissue differentiation and the detection of small morphological details. CMR at 7.0T improves spatial resolution versus today’s clinical protocols. This capability is as yet untapped in HCM patients. We aimed to examine the feasibility of CMR at 7.0T in HCM patients and to demonstrate its capability for the visualization of subtle morphological details.MethodsWe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…All HCM patients included in the study had previously undergone a clinical MRI exam including LGE imaging for detection of myocardial fibrosis 27 . For this purpose a 3.0 T MR system (Magnetom Verio, Siemens, Erlangen, Germany) was employed using a 32-channel RF receive array.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All HCM patients included in the study had previously undergone a clinical MRI exam including LGE imaging for detection of myocardial fibrosis 27 . For this purpose a 3.0 T MR system (Magnetom Verio, Siemens, Erlangen, Germany) was employed using a 32-channel RF receive array.…”
Section: Methodsmentioning
confidence: 99%
“…The overall distribution of septal T 2 * was analyzed using the histogram of the relative frequencies of T 2 * for all septal voxels in all subjects within the respective group. Evaluation of LV-morphology was described recently 27 .…”
Section: Methodsmentioning
confidence: 99%
“…CMR remains the pre-eminent imaging modality for assessing both tissue characterization and mechanical activation, and the increasing experience with ultrahigh field CMR will inevitably result in improved image quality [152,153]]. Greater spatial resolution will allow detailed visualization of the entire coronary venous tree allowing pre-procedural planning to be performed entirely from one, non-ionizing imaging modality.…”
Section: Five Year Viewmentioning
confidence: 99%
“…On the cardiac UHF MRI applications side, a recent study investigated high spatial resolution cardiac MRI in 13 patients with hypertrophic cardiomyopathy . The imaging protocol allowed for intraindividual comparison of patients imaged with 3T and 7T MR systems.…”
Section: Cardiovascularmentioning
confidence: 99%
“…The imaging protocol allowed for intraindividual comparison of patients imaged with 3T and 7T MR systems. The authors of this initial study concluded that 7T cardiac MRI is feasible in patients with hypertrophic cardiomyopathy, allowing for the detection of subtle morphological details in regions of extended hypertrophy and late gadolinium enhancement …”
Section: Cardiovascularmentioning
confidence: 99%